A Quantitative Comparison of High Latitude Electric Field Models During a Large Geomagnetic Storm - L. Orr; A. Grocott; M.‐T. Walach; G. Chisham; M. P. Freeman; M. M. Lam; R. M. Shore (Space Weather)
Abstract Models of the high‐latitude ionospheric electric field (EF) are commonly used to specify the magnetospheric forcing in thermosphere or whole atmosphere models. The use of decades‐old models based on spacecraft data is still widespread. Currently the Heelis et al. (1982, https://doi.org/10.1029/ja087ia08p06339) and Weimer (2005b, https://doi.org/10.1029/2005ja011270) climatology models are most commonly used but it is possible a more recent EF model could improve forecasting functionality. Modern EF models, derived from radar data, have been developed to incorporate advances in data availability (Bristow et al., 2022, https://doi.org/10.1029/2021sw002920; Thomas & Shepherd, 2018, https://doi.org/10.1002/2018ja025280; Walach et al., 2022, https://doi.org/10.1029/2021ja029559). It is expected that climatologies based on this larger and up‐to‐date data set will better represent the high latitude ionosphere and improve forecasting abilities. An example of two such models, which have been developed using line‐of‐sight velocity measurements from the Super Dual Auroral Radar Network (SuperDARN) are the Thomas and Shepherd model (TS18) (Thomas & Shepherd, 2018, https://doi.org/10.1002/2018ja025280), and Walach and Grocott geomagnetic Storm model (WGS21) (Walach et al., 2021, https://doi.org/10.1029/2020ja028512). Here we compare the outputs of these EF models during the September 2017 storm, covering a range of solar wind and interplanetary magnetic field (IMF) conditions. We explore the relationships between the IMF conditions and the model output parameters such as transpolar voltage, the polar cap size and the lower latitude boundary of convection. We find that the electric potential and field parameters from the spacecraft‐based models have a significantly higher magnitude than the SuperDARN‐based models. We discuss the similarities and differences in topology and magnitude for each model.